2007
DOI: 10.1080/10401230701653377
|View full text |Cite
|
Sign up to set email alerts
|

Should Depressive Syndromes Be Reclassified as “Metabolic Syndrome Type II”?

Abstract: A comprehensive management approach for depressive disorders should routinely include opportunistic screening and primary prevention strategies targeting metabolically mediated comorbidity (e.g., cardiovascular disease). Innovative treatments for mood disorders, which primarily target aberrant metabolic networks, may constitute potentially novel, and disease-modifying, treatment avenues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
153
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(170 citation statements)
references
References 77 publications
8
153
0
5
Order By: Relevance
“…It has been hypothesized that BD and metabolic syndrome share a set of common risk factors and overlapping pathophysiology 782, 783, 784. While medications used to treat BD, particularly atypical antipsychotics, can also lead to metabolic dysfunction and weight problems (Section 8), insufficient access to primary and preventative health care, low socioeconomic status, habitual inactivity, insulin dysfunction, peripheral inflammation and neuroinflammation, oxidative stress, and childhood adversity are also important contributors 785…”
Section: Specific Populationsmentioning
confidence: 99%
“…It has been hypothesized that BD and metabolic syndrome share a set of common risk factors and overlapping pathophysiology 782, 783, 784. While medications used to treat BD, particularly atypical antipsychotics, can also lead to metabolic dysfunction and weight problems (Section 8), insufficient access to primary and preventative health care, low socioeconomic status, habitual inactivity, insulin dysfunction, peripheral inflammation and neuroinflammation, oxidative stress, and childhood adversity are also important contributors 785…”
Section: Specific Populationsmentioning
confidence: 99%
“…Depression has been likened to a state of ''accelerated aging,'' affecting the hippocampus and the cardiovascular (CV), cerebrovascular, neuroendocrine, metabolic, and immune systems, [1][2][3] and depressed individuals have a higher incidence of various diseases often associated with aging, such as Type II diabetes, metabolic syndrome, osteoporosis, CV disease, stroke, and pathological cognitive aging, including Alzheimer's disease and other dementias. [2,[4][5][6][7][8] Depression is also associated with significantly worse outcomes in a number of medical conditions, and depression is an independent risk factor for early mortality (even after accounting for sociodemographic factors, suicide, and biological and behavioral risk factors, such as smoking, alcohol, and physical illness).…”
mentioning
confidence: 99%
“…The mood improvements associated with weight loss may be attributable to reductions in pathophysiological processes such as inflammation and hypothalamic-pituitary-adrenal axis activation that are common to both insulin resistance and mood disorders. [7] We examined the predictors of weight change among participants at S1 using multivariable analysis (Table 3). We found that each visit per month increase in the LI was associated with a 0.7 kg/m 2 greater loss in BMI after controlling for sex, age, baseline BMI and time spent in the programme.…”
Section: Fig 1 Weight Loss (%) Among Participants In Lis In Two Primentioning
confidence: 99%